Radioactivity Distribution In Surface And Core Sediment Of The Central Part Of The Algerian Coast: An Estimation Of The Recent Sedimentation Rate - NOUREDDINE, A.; BENKRID, M.; HAMMADI, A.; BOUDJENOUN, R.; MENACER, M.; KHABER, A.; KECIR, M.S. (Mediterranean Marine Science, 2003)
Sediment core samples and marine surface sediments of identical composition, mostly muddy, were collected using a Van Veen type grab and a box corer on board the M.S. Benyahia research vessel (ISMAL), along the Algerian littoral, between Algiers (36Ζ49.9 N/ 03Ζ 02.3 E) and Cherchell (36Ζ 39.4 N/ 02Ζ 12.4 E), during a sampling cruise in September 1997. The samples were analysed to determine the activity concentration of natural radionuclides (uranium and thorium series and 40 K as well) and artificial radionuclides ( 137 Cs and Pu isotopes), using a direct gamma spectrometry for gamma emitters and radiochemical separations and alpha spectrometry for alpha emitters. The horizontal and vertical distribution of the examined radionuclides were studied in the surface and core samples and an effort to estimate the sedimentation rate was attempted.The measured values range was: 17 - 26 Bq/Kg dry for uranium series radioisotopes, 18 – 32 Bq/Kg dry for thorium series radioisotopes, 311 - 690 Bq/Kg dry for 40 K, 0.4 - 11 Bq/Kg dry, for 137 Cs and 0.4 – 1.0 Bq/Kg dry for 239 + 240 Pu.